Comparative Transcriptome Analyses of the Developmental Stages of Taenia multiceps - Li, Wen-Hui; Yang, Yang; Zhang, Nian-Zhang; Wang, Jian-Kui; Liu, Yin-Ju; Li, Li; Yan, Hong-Bin; Jia, Wan-Zhong; Fu, Baoquan (Frontiers in Veterinary Science, 2021)
Cerebral coenurosis, caused by the larval stage of Taenia multiceps (Coenurus cerebralis) is a fatal central nervous system disease in sheep and other herbivores and occasionally in humans. The life cycle of T. multiceps consists of adult (Adu), Coenurus cerebralis and oncosphere (Onc) stages. Coenurus cerebralis is composed of cyst wall (Cyst), cyst fluid and protoscolices (Pro). The transcriptome profiles in the different developmental stages of the parasite remain unknown. In this study, RNA-seq was applied to identify transcriptions in the life cycle of T. multiceps, including Onc, Pro, Cyst and Adu, as well as scolex-neck proglottids (Snp), immature-mature proglottids (Imp) and gravid proglottids (Grp) of the adult stage. A total of 13,013 genes were identified, of which 2,437 genes were specific up-regulated in the different stages. The number of up-regulated genes in Adu was higher than in the other three stages. Additionally, 1,228 genes were specific up-regulated in different tissues of the adult stage, and the number of up-regulated genes in Imp was more than Snp and Grp. Go and KEGG analysis showed that the specific up-regulated genes mainly participate in cellular and metabolic processes, binding and catalytic activity, genetic information processing, and environmental information processing. Besides, a large number of genes related to the development and parasites-host interaction were identified. qRT-PCR validated that the transcriptomic levels of the selected 14 DEGs were basically consistent with those in RNA-seq. The present study provides insights into the mechanism of developmental biology and the parasitic life of T. multiceps.